(untitled) (Uzbek Scholar Journal, 2023)
The article covers the issues of developing the organization of production based on digital technologies in industrial enterprises, analyzes existing problems in this field, studies the factors hindering digitalization processes, and describes the directions of digitalization of production. Features of modern digital production systems are revealed.